2022
DOI: 10.1101/2022.07.20.499551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of cardiomyocytes from human induced pluripotent stem cells resembling atrial cells with ability to respond to adrenoceptor agonists

Abstract: Cardiovascular disease is the leading cause of global mortality and morbidity. Cardiac dysrhythmias contribute significantly to this disease burden. Atrial fibrillation (AF) is the most common chronic dysrhythmia. Human induced pluripotent stem cell-derived atrial cardiomyocytes (hiPSC-AMs) present an exciting new model for AF but currently fail to reach maturity and so are limited in translational potential currently. We report a new approach using a combination of Gremlin 2 and retinoic acid treatment of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Pioneering studies have successfully recapitulated cardiac development in a dish, resulting in the generation of functional ventricular, atrial, and even specialized conduction system cells including SANPCs (Devalla et al, 2015; Hausburg et al, 2017; Lee et al, 2017; Li et al, 2021; Protze et al, 2017, 2019; Ren et al, 2019; Zhang et al, 2011; Zhao, Shao, et al, 2020). Despite significant strides in differentiating human pluripotent stem cells into ventricular or atrial myocytes (Ahmad et al, 2023; Cyganek et al, 2018; Devalla et al, 2015; Lee et al, 2017; Zhang et al, 2011), the directed differentiation toward SANPCs has relatively lagged behind. The distinct molecular and functional characteristics of cardiac pacemaker cells, which confer their cardiac pacemaking properties, present unique challenges in recreating these cells in vitro (Barbuti & Robinson, 2015; Christoffels et al, 2010; Kapoor et al, 2013; Liang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering studies have successfully recapitulated cardiac development in a dish, resulting in the generation of functional ventricular, atrial, and even specialized conduction system cells including SANPCs (Devalla et al, 2015; Hausburg et al, 2017; Lee et al, 2017; Li et al, 2021; Protze et al, 2017, 2019; Ren et al, 2019; Zhang et al, 2011; Zhao, Shao, et al, 2020). Despite significant strides in differentiating human pluripotent stem cells into ventricular or atrial myocytes (Ahmad et al, 2023; Cyganek et al, 2018; Devalla et al, 2015; Lee et al, 2017; Zhang et al, 2011), the directed differentiation toward SANPCs has relatively lagged behind. The distinct molecular and functional characteristics of cardiac pacemaker cells, which confer their cardiac pacemaking properties, present unique challenges in recreating these cells in vitro (Barbuti & Robinson, 2015; Christoffels et al, 2010; Kapoor et al, 2013; Liang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In hiPSC-aCMs derived from RA-guided differentiation, I Kur is relatively smaller than adult atrial cells but was sufficient to produce a shorter APD compared to hiPSC-vCMs (Hilderink et al, 2020). Otherwise, I Ca,L , I Kr , and I Ks current densities and the expression of their encoding channels are considered comparable to adult cardiomyocytes (Itzhaki et al, 2011;Ma et al, 2011;Lahti et al, 2012), and I KAch was recently shown to be comparable in hiPSC-aCMs (Ahmad et al, 2023).…”
Section: Ion Channel Expression Profiles and Maturationmentioning
confidence: 96%
“…They showed low resting membrane potentials [33], low/ absent I K1 [34], low membrane capacitances [35], immature AP profiles and slow electric impulse propagation velocities [32], and their generation primarily focused on ventricular rather than atrial phenotypes. However, Ahmad et al [36] describe hiPSC-CMs with AP properties and acetylcholine (ACh)-activated I K expression characteristic of atrial cells. iPSCs have also been explored as possible models for normal and disease-related changes in ion channel expression, Ca 2+ homeostatic phenotypes, neurocardiac interactions and cardiac hypertrophic change (see: Chen et al [37]; Zhou et al [38]; Li et al [39] and Langa et al [40], respectively).…”
Section: Modern Developments In the Fieldmentioning
confidence: 99%
“…Closer characterization of such signalling pathways in iPSC cells is a relatively new area of study. Ahmad et al [36] describe differentiated human iPSCs resembling an atrial phenotype, with the expected electrophysiological and Ca 2+ signalling properties, and specific transcripts, responsive to adrenergic stimulation, therefore permitting studies of such effects.…”
Section: Autonomic G-protein-mediated Modulationmentioning
confidence: 99%
See 1 more Smart Citation